New in situ method for the determination of the crystallization kinetics of glass‐ceramics. Issue 12 (3rd September 2020) - Sander, Malte; Jacobs, Philipp; Roos, Christian
Abstract: An in situ method for the characterization of the crystallization behavior of glass‐ceramics has been developed, which is based on an acoustic, nondestructive Young's modulus measurement technique according to ASTM E1876. The progression of the crystallization can be measured due to an increasing Young's modulus during the heat treatment, which is a result of the formation of solid precipitations in a viscous melt. The crystalline content can be deduced from the data using a superposition principle for elastic properties. The developed method was evaluated using bar‐shaped bulk glass samples from a lithium‐alumosilicate glass‐ceramic system. The sample geometry, with its low surface‐to‐volume ratio, allowed a detailed analysis of the volume crystallization, due to a reduced influence of the surface crystallization on the measured signal. The development of the crystalline content was confirmed, and variations in the surface and bulk crystallization were examined using a reference method based on X‐ray diffraction.